Brain Functional Alterations and Association with Cognition in People with Preclinical Subjective Cognitive Decline and Objective Subtle Cognitive Difficulties. (1st March 2023) - Ren, Shuhua; Li, Junpeng; Huang, Lin; Huang, Qi; Chen, Kewei; Hu, Jingchao; Jessen, Frank; Hu, Xiaochen; Jiang, Donglang; Zhu, Lin; Wang, Xiaomin; Guan, Yihui; et al.
Highlights: Objective subtle cognitive difficulties (Obj-SCD) showed Aβ in AD-related regions. Aβ was associated with cognition in Obj-SCD. Aβ was only associated with execution in SCD. FDG was associated with execution only in Obj-SCD. Abstract: Subjective cognitive decline (SCD) and objective subtle cognitive difficulties (Obj-SCD) are considered the initial stages of aberrant cognition prior to mild cognitive impairment (MCI) due to Alzheimer's disease (AD). We aimed to determine the difference of brain function of SCD and Obj-SCD, furthermore, to figure out which one could be the marker of early AD. One hundred and eighty-five participants were enrolled in this study to determine the amyloid pathology and glucose metabolism changes in SCD and Obj-SCD. The association of amyloid deposition and glucose metabolism with cognitive domains were also investigated. Obj-SCD displayed significantly increased amyloid deposition in frontal and temporal lobes compared to SCD and normal cognitive control (NCC). No difference of amyloid deposition between SCD and NCC, and no difference of glucose metabolism among the three groups were observed. Amyloid deposition was associated with function of memory, language and executive domains, and glucose metabolism was only associated with executive function in Obj-SCD. Amyloid deposition was only associated with executive function in SCD. Obj-SCD could be the early stage of AD, which displayed significant increased amyloid deposition, and the increased amyloid deposition was associated with cognitive function in different domains.